Bless the rains down in Africa : How can Finnish companies successfully enter Sub-Saharan African markets? - Jokinen, Ville (My University, 2023)
It is widely known that Africa is full of potential and opportunities for foreign companies to expand and invest and that potential and opportunities do not come without risks posed by the African business environment. At the same time, affirmative long-term investment decisions and the implementation of sustainable agendas are hampered by the overwhelming social, political, and economic risks that companies in Africa must contend with. This thesis and its study aim to cover the research gap in the literature by investigating what types of risks Finnish companies can encounter when they enter Sub-Saharan African markets as well as how institutions and resources affect successful market entry and can help mitigate or avoid the risks. Based on this, the main research question that this thesis aims to answer is: How can Finnish companies successfully enter Sub-Saharan African markets? Previous research and academic literature have identified certain market characteristics that define the Sub-Saharan African business environment as well as risks that are often associated with the business environment of Sub-Saharan Africa. Institutions and resources were identified as key factors affecting market entry in international business discipline and elements such as institutional distance, institutional voids, and resource commitment were identified to strongly affect market entry in emerging markets such as Sub-Saharan Africa. The empirical data for this study was collected through expert interviews where experts from Finnish export promotion services organizations were interviewed along with Finnish entrepreneurs/companies that currently operate in Sub-Saharan Africa. Additionally, news articles and online publications from trusted media outlets were used as secondary data source to strengthen the primary empirical data. The findings from empirical data mostly confirm that Finnish companies entering Sub-Saharan Africa encounter the same risks as well as are affected by the same institutional and resource-based factors during the market entry process as covered in previous research and academic literature. The aim of this study was met by creating practical implications for Finnish companies planning to enter Sub-Saharan African markets based on the theoretical background and empirical data of this study. Practical implications of this study identified a set of five practical recommendations for Finnish companies to successfully enter Sub-Saharan African markets – have alternatives, know your key competencies, have a physical presence, utilize external support, and build partnerships.

Yksi 2000-luvun trendikkäimmistä väittämistä kansainvälisessä liiketoiminnassa on ollut Afrikan potentiaali ja mahdollisuudet ulkomaisille yrityksille, sekä mahdollisuus hyötyä laajentumisesta ja investoinneista Afrikkaan. Afrikan potentiaaliin ja mahdollisuuksiin liittyy kuitenkin myös riskejä, joita sen liiketoimintaympäristön hankaluus aiheuttaa. Esimerkiksi pitkän aikavälin investointipäätöksiä ja kestävän kehityksen ohjelmien toteuttamista haittaavat suuret sosiaaliset, poliittiset ja taloudelliset riskit, joiden kanssa yritysten on kamppailtava Afrikan markkinoilla. Tämän pro gradu -tutkielman ja sen tutkimuksen tavoitteena on kattaa kirjallisuudessa oleva tutkimusaukko selvittämällä, minkälaisia riskejä suomalaiset yritykset voivat kohdata Saharan eteläpuolisen Afrikan markkinoilla ja miten sekä instituutiot että resurssit vaikuttavat onnistuneeseen markkinoillepääsyyn, ja voivat jopa auttaa riskien lieventämisessä tai välttämisessä. Tämän pohjalta tutkielman päätutkimuskysymys on: Miten suomalaiset yritykset voivat onnistuneesti päästä Saharan eteläpuolisen Afrikan markkinoille? Aiemmissa akateemisissa tutkimuksissa on yksilöity tiettyjä erityisominaisuuksia, jotka kuvastavat Saharan eteläpuolisen Afrikan liiketoimintaympäristöä sekä riskejä, jotka usein liittyvät Saharan eteläpuolisen Afrikan liiketoimintaympäristöön. Lisäksi kansainvälisen liiketoiminnan tutkimuksen saralla myös instituutioiden ja resurssien on todettu olevan keskeisiä tekijöitä, jotka vaikuttavat yritysten markkinoillepääsyyn. Tutkimuksen empiirinen aineisto kerättiin asiantuntijahaastatteluilla, joita tuettiin tunnettujen medioiden uutisartikkeleilla ja internet-julkaisuilla. Haastatteluissa haastateltiin suomalaisten vienninedistämispalveluorganisaatioiden asiantuntijoita sekä Saharan eteläpuolisessa Afrikassa tällä hetkellä toimivia suomalaisia yrittäjiä/yrityksiä. Empiirisestä aineistosta saadut tulokset vahvistavat suurimmilta osin sen, että Saharan eteläpuoliseen Afrikkaan pyrkivät suomalaiset yritykset kohtaavat markkinoillepääsyn aikana samoja riskejä sekä samoja instituutioihin ja resursseihin liittyviä tekijöitä, joita on jo käsitelty aiemmissa akateemisissa tutkimuksissa. Tutkimuksen tavoite saavutettiin luomalla joukko käytännön suosituksia suomalaisyrityksille, jotka suunnittelevat markkinoillepääsyä Saharan eteläpuolisen Afrikkaan. Suositukset perustuvat pro gradu -tutkielman teorian ja empiirisen aineiston perusteella kerättyyn dataan ja niiden avulla tunnistettiin viisi suositusta onnistuneeseen markkinoillepääsyyn Saharan eteläpuoliseen Afrikkaan – pidä vaihtoehdot avoinna, tunne osaamisesi, ole fyysisesti paikalla, hyödynnä ulkoista tukea sekä rakenna kumppanuuksia.
Keywords: Finnish, company, market entry, market entry strategy, uncertainty, risk, institution, institutional environment, resource